Chemical Modification of Neem (Azadirachta indica) Biomass as Bioadsorbent for Removal of Pb2+ Ion from Aqueous Waste Water - Nigist Awish Hatiya; Ali Shemsedin Reshad; Zemene Worku Negie (Adsorption Science & Technology)
In this study, neem biomass (a mixture of neem leaf and bark), obtained from the matured neem tree, which is an eco-friendly and low-cost material was selected as a bioadsorbent to remove lead metal ion (Pb2+) from aqueous solutions. Neem biomass-based bioadsorbent having a carboxylic group was prepared by activation using chemical modification by NaOH and citric acid with a very simple method. The optimal activation conditions were determined as 37 min, 120°C, in 0.73 M citric acid, with a sample/acid ratio of 1/100 (mass/volume). To determine the basic properties such as chemical structure, porosity, and surface properties of the neem biomass (NB) and chemically modified neem biomass (CMNB), they were characterized by BET, FTIR, SEM, XRD, and pHpzc methods. It was observed that activation has improved the adsorption capacity of the NB and also caused a more amorphous structure. The effects of adsorption parameters such as pH (2–7), contact time (10–110 min), initial Pb2+ ion concentration (100–300 g/L), and bioadsorbent dosage (01–1.1 g/L) on percentage removal of Pb2+ ion were studied. Maximum removal of Pb2+ ion (97.29%) was recorded at 0.9 g/L bioadsorbent dosage, 50 min contact time, pH of 6, and initial metal ion concentration of 100 mg/L. Kinetics and isotherm studies showed that the adsorption mechanism of Pb2+ ion using CMNB follows pseudosecond-order while isotherm studies fit with both models but, relatively, Freundlich model better fit having a little higher R2=0.9804. The outcome specifies that the modified bioadsorbent can be utilized as a good and low-cost alternative for the treatment of effluent containing lead (II) ions in water.